Whole genome analysis of Hawksbill turtles in Singapore reveals their genetic adaptations to disease and sensory perception - Desai, Archita Sanjay (Nanyang Technological University, 2024)
Hawksbill sea turtles (Eretmochelys imbricata) are critically endangered species found in tropical waters around the world. Their populations are threatened by various anthropogenic factors like rising temperatures associated with climate change. Hawksbill turtles have high conservation importance due to their role in maintaining healthy reef ecosystems. However, there is limited information available about their behaviour and life-history owing to their complex migration and life-cycle patterns. Genetic studies are crucial to understand their environmental adaptations and develop appropriate conservation plans. This pioneering study analyses whole genomes of hawksbill turtles in Singapore to understand how they are adapted to their environment, and determine which genes underwent recent positive selection. The whole genomes of 18 hawksbill turtle individuals with 3.6 million single nucleotide polymorphisms (SNPs) were analysed to identify regions of positive selection. This was done by computing Integrated Haplotype Homozygosity Scores (iHS) and demarcating regions of disproportionately high haplotype homozygosity. The biological and molecular processes influenced by the genes located within these regions was determined by Functional Enrichment Analysis (FEA). Based on the results of this study, 94 genes located across the whole genome likely underwent positive selection. These genes are mainly associated with disease response, olfactory system, cell signalling and cellular transport. This study's findings explain how Hawksbill turtles are adapted to navigate using olfaction, fight against infections, and survive during their unique life-cycles and large-scale migrations. Understanding such genetic adaptations is key to predicting their response towards climate change and other environmental stressors.